Pengaruh Medan Magnet pada Pembawa Muatan Lapisan Klorofil Spirulina sp Hasil Spin Coating: Septinia Qoirun Nisa, Utari, Budi Purnama - Septinia Qoirun Nisa, Septinia Qoirun Nisa; Utari, Utari; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
The magnetic field effect on the charge carrier of Spirulina sp thin filmsby spin coating fabrication by mean a I-V measurements is reported in this paper. Magnetoconductance measurements showed that the field required to achieve the saturated currentof sample B is smaller than the sample A. This indicated the mechanism of charge carrier recombination attribute to the degree of purity. Finally, a MC ratio of 37.4% and 50.6% was obtained for sample A and sample B, respectively.